2019
DOI: 10.3389/fped.2019.00242
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for Kawasaki Disease: Clinical Utility and the Challenges Ahead

Abstract: Kawasaki disease (KD) has replaced acute rheumatic fever as the most common cause of acquired heart disease in children in the developed world and is increasingly being recognized from several developing countries. It is a systemic vasculitis with a predilection for coronary arteries. The diagnosis is based on a constellation of clinical findings that appear in a temporal sequence. Quite understandably, this can become a problem in situations wherein the clinical features are not typical. In such situations, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 91 publications
1
50
0
Order By: Relevance
“…Myocardial involvement in acute KD is universal from histologic and functional perspectives; hence, the role of NT-proBNP as a potential biomarker has been extensively studied ( 25 , 26 ). Kim et al ( 27 ) described cardiac troponin I (cTnI) in relation to KD and showed a significant increase in cTnI level in the acute stage of KD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Myocardial involvement in acute KD is universal from histologic and functional perspectives; hence, the role of NT-proBNP as a potential biomarker has been extensively studied ( 25 , 26 ). Kim et al ( 27 ) described cardiac troponin I (cTnI) in relation to KD and showed a significant increase in cTnI level in the acute stage of KD.…”
Section: Discussionmentioning
confidence: 99%
“…This increase was statistically significant in CAL patients. Although some studies have recognized both thrombocytopenia and significant thrombocytosis as predictors of CAAs or IVIG resistance ( 25 , 38 ), another study showed no association ( 24 ). The exact mechanism underlying thrombocytosis is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have focused on cytokines and chemokines during acute KD. However, these proteins are relatively non-specific and are elevated in many inflammatory processes ( 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported to be positively correlated with impairment of ventricular relaxation in patients with KD (27). Gamma-glutamyl transferase and alanine transferase, however, have not been found to be useful in establishing a clinical diagnosis of KD (40).…”
Section: Other Cardiac Biomarkersmentioning
confidence: 99%